2015
DOI: 10.1007/s12028-015-0117-x
|View full text |Cite
|
Sign up to set email alerts
|

Red Blood Cell Distribution Width is Associated with Poor Clinical Outcome After Subarachnoid Hemorrhage: A Pilot Study

Abstract: An elevated RDW is associated with poor outcome in SAH patients. RDW may be a useful predictor of outcomes after SAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 54 publications
1
35
0
Order By: Relevance
“…Among the 1008 OHCA patients who had ROSC, the highest RDW (≥ 15.0%) quartile in admitted ED patients was independently associated with an increased risk of mortality during the 30-day period (HR 1.39). Additionally, RDW showed significantly elevated values in subarachnoid hemorrhage (SAH) patients and cerebral infarction patients with poor outcomes 34,35 . Although cardiovascular disease is known to be the main cause of OHCA, stroke may also be a cause.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 1008 OHCA patients who had ROSC, the highest RDW (≥ 15.0%) quartile in admitted ED patients was independently associated with an increased risk of mortality during the 30-day period (HR 1.39). Additionally, RDW showed significantly elevated values in subarachnoid hemorrhage (SAH) patients and cerebral infarction patients with poor outcomes 34,35 . Although cardiovascular disease is known to be the main cause of OHCA, stroke may also be a cause.…”
Section: Discussionmentioning
confidence: 99%
“…Our recently published results and previous findings suggest that abnormal red blood cell (RBC) indices are correlated with poor outcomes in survivors with acute stroke or cognitive dysfunction after aneurysmal subarachnoid hemorrhage (aSAH) (10)(11)(12). Therefore, we hypothesized that RBC indices might be related to cognitive functioning after ICH onset.…”
Section: Introductionmentioning
confidence: 94%
“…2 However, recent studies revealed that RDW is useful in estimating the risk, prognosis or disease activity of non-haematologic diseases, such as cardiovascular diseases, [3][4][5][6][7] liver diseases, 8,9 autoimmune diseases [10][11][12] or stroke. 13 In patients with acute subarachnoid haemorrhage (SAH) 14,15 or acute cerebral infarction, 16 RDW was proved to be associated with short-term and functional outcome of patients. However, whether RDW is associated with long-term outcome of SAH remains unknown.…”
Section: Introductionmentioning
confidence: 99%